Exploring lactylation and cancer biology: insights from pathogenesis to clinical applications - Gou, Zixuan; Sun, Qianchuang; Li, Jiannan (Frontiers in Cell and Developmental Biology, 2025)
As a byproduct of glycolysis, lactate functions as a signaling molecule, a substrate for energy metabolism, and a regulator of the tumor microenvironment (TME). It is involved in various biological processes, including energy shuttling, tumor growth and invasion, drug resistance, and immune evasion. Lactylation, a recently identified post-translational modification (PTM), acts as a bridge between gene regulation and cellular metabolism, thus playing a crucial role in tumor biology. Similar to other epigenetic modifications, lactylation influences the spatial conformation of chromatin, modulates DNA accessibility, and regulates gene expression. It intricately participates in TME-related processes by orchestrating immune state transitions and enhancing the malignant characteristics of tumors. This review summarizes lactylation-related genes in tumors, the role of lactylation in the TME, the interactions of the genes with other metabolic pathways, and the potential mechanisms underlying tumor progression as well as their clinical implications. Despite its nascent stage, research on the epigenetic regulation of tumor-related genes by lactylation holds promise. In this review, we highlighted unresolved challenges in this field and provided insights that may guide the development of novel targeted therapies for cancer.